2020
DOI: 10.2147/vhrm.s230041
|View full text |Cite
|
Sign up to set email alerts
|

<p>Systemic Arterial Stiffness in New Diagnosed Idiopathic Pulmonary Arterial Hypertension Patients</p>

Abstract: Objective: We suggested: 1) patients with idiopathic pulmonary hypertension (IPAH) have active factors which could damage not only the pulmonary but systemic arteries too as in arterial hypertensive patients; 2) if these changes were present, they might correlate with other parameters influencing on the prognosis. This study is the first attempt to use cardioankle vascular index (CAVI) for the evaluation of systemic arterial stiffness in patients with IPAH. Methods: A total of 112 patients were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 71 publications
1
11
1
Order By: Relevance
“…In our study, patients with acute PE showed significantly increased echo-derived arterial stiffness compared with normal subjects and hypertensive patients, as already reported in PAH patients [ 39 ]. The increased CAVI found in our PE cohort was not statistically different from our IPAH cohort, although a trend to higher values was observed in the latter population.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, patients with acute PE showed significantly increased echo-derived arterial stiffness compared with normal subjects and hypertensive patients, as already reported in PAH patients [ 39 ]. The increased CAVI found in our PE cohort was not statistically different from our IPAH cohort, although a trend to higher values was observed in the latter population.…”
Section: Discussionsupporting
confidence: 88%
“…Recently we published the results of our study on the comparison of arterial stiffness parameters in patients with IPAH, systemic hypertension, and healthy people who were adjusted to age. 44 We established that mean CAVI was the highest in the group with systemic hypertension, but did not differ significantly from mean CAVI in the group newly diagnosed with IPAH. The healthy persons had significantly reduced CAVI, PWVm and PWVe values than patients with IPAH, despite the comparable office and aorta blood pressure.…”
Section: Discussionmentioning
confidence: 77%
“…We evaluated the systemic artery stiffness parameters in patients with newly diagnosed IPAH and in essential hypertensive patients. 44 We found the mean cardio-ankle vascular index (CAVI), which is independent of the blood pressure characteristic of arterial stiffness, 45 was increased significantly in IPAH patients compared to the healthy group and did not much differ from one in systemic hypertensives matched to age. Also, the CAVI correlated with IPAH patient functional capacity and right ventricle function.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“… 9 Recently, Radchenko et al reported that arterial stiffness evaluated by CAVI was significantly higher in patients with pulmonary arterial hypertension (PAH) than in healthy subjects. 10 These findings suggest that increased arterial stiffness may increase afterload of LV and may affect cardiac function in patients with pulmonary hypertension (PH) including CTEPH. Therefore, arterial stiffness may play an important role in the pathophysiology of CTEPH.…”
Section: Introductionmentioning
confidence: 99%